An adhesive, anti-freezing, and environment stable zwitterionic organohydrogel for flexible all-solid-state supercapacitor. (21st July 2022) - Hu, Oudong; Lu, Jing; Weng, Sen; Hou, Linxi; Zhang, Xi; Jiang, Xiancai
Abstract: High-performance hydrogel electrolyte is a candidate material for flexible all-solid-state supercapacitor. However, there are some challenges limiting the application of hydrogel electrolyte in supercapacitors, such as poor interfacial contact between gel electrolyte and solid electrode, freezing at low temperature, and environmental instability. Herein, an adhesive, anti-freezing and environment stable poly(vinyl alcohol)/poly(acrylamide- co -[2-(methacryloyloxy) ethyl] dimethyl-(3-sulfo-propyl) ammonium hydroxide)/CaCl2 (PVA/P(AM-co-SBMA)/CaCl2, PASC) organohydrogel electrolyte was successfully fabricated. Non-zwitterionic components (PVA, AM) were introduced into the organohydrogel network to construct the double network zwitterionic organohydrogel. Meanwhile, appropriate amount of CaCl2 was introduced into the gel network to promote the formation of P(AM-co-SBMA) chain entanglement structure, which could significantly dissipate energy to toughen the organohydrogel and achieve favorable mechanical properties (tensile strength 216 ± 15 kPa, Young's modulus 311 ± 15 kPa). In addition, abundant zwitterionic polymers and hydroxyl groups endowed the organohydrogel with favorable adhesion. An excellent water retention capacity and satisfactory low-temperature tolerance based on the synergistic effect of zwitterionic polymers, glycerol and CaCl2 was endowed to PVA/P(AM-co-SBMA)/CaCl2 organohydrogel. Based on the above favorable performance, a flexible all-solid-state supercapacitor was constructed by sandwiching organohydrogel electrolyte between two CNT film electrodes. Impressively, the flexible all-solid-state supercapacitor delivered a wide potential window (0–2.1 V), and exhibited a long cycling life (7000 cycles) and a high-capacity retention (82.4%). Moreover, based on the tight contact between electrolyte and electrode, the device showed superior electrochemical stability even under harsh deformations such as hammering and bending. It was believed that this work provided a significant method for developing high-performance organohydrogel electrolytes for flexible all-solid-state supercapacitor. Graphical abstract: Image 1 Highlights: A facile preparation method for PVA/P(AM-co-SBMA) polyzwitterionic organohydrogel electrolyte was presented. PVA/P(AM-co-SBMA) polyzwitterionic organohydrogel showed high tolerance for extreme low temperature. The abundant zwitterionic polymers and hydroxyl groups endowed the organohydrogel with favorable adhesion. The all-solid-state supercapacitor presented a broad potential window and deformation resistance.